The effect of garden use on quality of life and behavioral and psychological symptoms of dementia in people living with dementia in nursing homes: a systematic review - Velde-van Buuringen, Melanie van der; Hendriks-van der Sar, Rosalie; Verbeek, Hilde; Achterberg, Wilco P.; Caljouw, Monique A. A. (Frontiers in Psychiatry, 2023)
Objectives: Considering the importance of going outside in a natural environment for people in general, and people living with dementia in particular, we want to unravel the aspects by which garden use affects quality of life (QoL) and behavioral and psychological symptoms of dementia (BPSD) in people living with dementia in nursing homes. Design: Systematic review. Setting and participants: People living with dementia in nursing homes. Methods: This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Eight electronic bibliographic databases were searched (May 2022). Quantitative, qualitative and mixed-methods studies describing the effect of garden use on QoL, BPSD, or other outcomes related to QoL or BPSD in people living with dementia in nursing homes were included. The methodological quality of individual studies was assessed with the Mixed Methods Appraisal Tool (MMAT) and a narrative synthesis of the results was performed. Results: After screening title and abstract (N = 498), and full-text assessment (N = 67), 19 publications were included. These described 17 studies and three types of interventions: (1) interventions regarding the evaluation of effects of specifically designed gardens; (2) participation of the people living with dementia in outside activities; and (3) other interventions, for example, garden visits and different seasons. Conclusions and implications: Overall, first studies appear to suggest positive effects of garden use on QoL, BPSD, or other outcomes related to QoL or BPSD (stress, sleep, mood) in people living with dementia in nursing homes. However, consensus regarding measurements and key outcomes, taking into account the physical, social, and organizational aspects when designing the garden use intervention, is necessary for the reliable evaluation of these interventions.